PENGARUH GAME ONLINE TERHADAP MINAT BELAJAR SISWA KELAS IV PADA MATA PELAJARAN BAHASA INDONESIA DI MI ISLAMIYAH PERGURUAN PALEMBANG - Meilin Faiza Pramuswari; Aquami; Siti Fatimah (STKIP Subang, 2025)
This study aims to analyze the influence of the online game Free Fire on the learning interest of fourth-grade students in the Indonesian language subject at MI Islamiyah Perguruan Palembang. The research uses a quantitative approach with an ex-post facto design. The sample consisted of 28 students. Data collection techniques included observation, questionnaires, interviews, and documentation. The results of the study show a significant influence between the intensity of playing online games and students’ learning interest. A significance value of 0.015 (<0.05) indicates that the online game Free Fire contributes 20.8% to learning interest. Students who play games excessively experience decreased focus, motivation, and activeness in participating in learning activities. The study concludes that collaboration between teachers and parents is needed in regulating students’ gaming duration so that it does not interfere with the academic process.